Analysis Factors that Influence Purchase Intention Based on Brand Trust for Electric Cars - Lady, Lady; Angelino, Kevin (STKIP Singkawang, 2024)
This research aims to examine the factors that influence the purchase intention of electric cars or battery electric vehicles (BEV). This research describes the development of purchasing interest and the attraction of Indonesian people towards electric cars. The research method used in this research was Smart PLS, with a total of 242 respondents, the sample of which was Indonesian people who have an interest in buying electric car products in Indonesia. The data collection technique used in this research was a questionnaire. The data analysis technique used was Smart PLS. The research results showed that brand awareness, brand image, social media marketing, and electronic word of mouth had a significant positive effect on brand trust, brand trust had a significant positive effect on purchase intention, brand image had a significant effect on purchase intention with brand trust as the mediation. However, perceived quality had no significant positive effect on brand trust. This research was one of the few studies discussing electric cars in Indonesia, focusing on factors that influence purchase intention, with brand trust as a mediator.